Development of a Cognitive Behavior Therapy Counseling Guide using Cognitive Restructuring Techniques to Reduce Anxiety in Middle School Bullying Victims - Ni Luh Deantini Ni Luh Deantini; Kadek Suranata; Wayan Eka Paramartha (Bisma The Journal of Counseling, 2025)
A sense of safety at school supports students in achieving both psychological and academic well-being, whereas feeling unsafe can lead to emotional disturbances such as anxiety, which hinders their overall development and academic performance. One major cause of anxiety among students is bullying by peers, which often results in victims becoming reluctant to attend school or even wanting to drop out. Although school Guidance and Counseling teachers have provided services and conducted home visits, their efforts remain suboptimal due to the lack of specific guidelines for addressing anxiety in bullying victims. This study aims to assess the content validity, acceptability, and effectiveness of a counseling manual based on cognitive behavior therapy using cognitive restructuring techniques to reduce anxiety in bullied students. The study was developed using the 4D model (Define, Design, Develop, and Disseminate), and the results showed that the product validity reached a CVR score of 1 and a CVI score of 0.011, falling within the appropriate category; the manual's acceptability scored 0.97, categorized as highly appropriate; and its effectiveness, with a p-value < 0.05, indicates that the manual is effective in reducing anxiety in victims of bullying. This cognitive behavior therapy-based counseling manual has been found beneficial in helping students manage anxiety caused by bullying, enabling them to participate in school activities without fear or worry.